THE Analisis Kekuatan Pada Komposit Matriks Epoxy Yang Diperkuat Dengan Serat Sisal Dan Serbuk Kayu Jati Pada Spakbor Motor - Mei Asih, Muhammad Hafizh Dhiyaul-haq (JURNAL ENGINEERING, 2025)
Composite material is a combination of two or more materials that are macroscopically bonded. This study aims to evaluate the effect of variations in sisal fiber and teak wood dust mixed with epoxy resin on tensile, bending, and impact strength. The research method was carried out experimentally with a resin composition of 90% and fiber-dust variations: 7% sisal + 3% wood dust, 5% sisal + 5% wood dust, and 3% sisal + 7% wood dust. The test results showed that the composite with a sisal fiber fraction of 7% and 3% wood dust had the highest tensile strength, which was 48.28 N/mm². Meanwhile, the 5% sisal + 5% wood dust fraction produced a tensile strength of 37.27 N/mm², and the 3% sisal + 7% wood dust fraction was 25.50 N/mm². This means that the higher the sisal fiber content, the higher the tensile, bending, and impact strength. Static analysis showed the highest von Mises stress value at a speed of 180 km/h, while the lowest stress occurred at a speed of 70 km/h. Overall, the static analysis results indicated a very low risk of plastic deformation or failure, making this composite material safe for use.